Evaluating Female Experiences of Electronic Dating Violence in Jordan: Motivations, Consequences, and Coping Strategies - Alsawalqa, Rula Odeh (Frontiers in Psychology, 2021)
Gender stereotypes can influence electronic dating violence (EDV) because the victims’ experiences with abusers depict crucial social mechanisms concerning relational dependency and unequal power relations between men and women, making it difficult for women to resist, report, or escape cyber abuse. In the Arab context, cyber abuse in romantic relationships has not been sufficiently examined. This study investigated female victims’ experiences of EDV through a qualitative exploratory descriptive approach. Participants experienced several short- and long-term negative psychological and emotional behavioral responses. Our findings validate that EDV heightened the probability of intimate partner violence definitively via psychological, emotional, verbal, and physical abuse. Their resistance strategies differed according to the extent and nature of the abuse. None of the victims sought help from family due to fear of being killed or forced out of university, and realizing that they would continue to experience multiple forms of abuse. Rather, they either sought help from female professors at the university or paid the abuser to be left alone. Further, they engaged in protective behaviors to block their abusive partner’s access to them, consulted an Information Technology expert, and secretly requested assistance from the police. Preference for controlling and dominant roles, gaining monetary benefits, sexual exploitation, peer pressure, and revenge and anger due to abandonment were the leading motivations for abuse. Female students in their first year of university, those who lived in a disjointed family environment, or those who suffered abuse from their families were particularly susceptible to being victimized. Moreover, passwords shared with others or accounts left open on others’ devices also enabled EDV. Hence, universities must conduct awareness sessions, for female students, on how to manage emotions and safe communication on social media and build healthy friendships and relationships. Curricula, seminars, workshops, and courses in the Jordanian educational sector should include programs and interventions that challenge perceived gender norms. These results have significant practical and clinical implications that help understand EDV in a poorly understood context and provide the groundwork for further research on the EDV problem in Jordan, addressing a lacuna in the literature on violence against Jordanian women.